Conclusion - Abdul Rahim, Roslina; Othman, Ahmad Faidzal; Kamarulzaman, Mohd Nazli (IIUM Press, 2023)
It must be agreed that COVID-19 is a challenging time and has significantly impacted many aspects of life, including academia and research. It introduces a new norm to the world and imparts substantial changes to the way researchers work as well. During these contesting times, we could observe how the trend has evolved and progressed globally in both medical sciences and clinical research. Although the movement restriction orders rendered many facilities to restrict the accessibility to researchers, the research may resume but with many twists. In basic medical science, most research works encompass collecting data from humans, animals, tissues, and ongoing laboratory work. Of course, some works involving the latter may halt during the pandemic. Nevertheless, we have perceived a build-up of research work that used established data from previous works, analysing them to write systematic reviews. Some epidemiological researchers gathered accessible data from local agencies to produce descriptive epidemiology studies. Of course, measuring the impact of the pandemic on the population has been prevailing during this time. In this kind of research, the data collection methodology has shifted from face-to-face interviews to online questionnaire surveys when appropriate. We have also witnessed that the pandemic proves to be a good time for researchers to analyse, present, and publish their data gathered during the pre- COVID era. In response to the travel restriction, many events, including the Medical Research Symposium 2021, were transformed into virtual or hybrid events to allow the utmost participation from researchers worldwide. It proves that the pandemic has somehow trained us to adapt and be responsive to external changes.